Computer networks and Internets - Comer, Douglas (Pearson Education, 2015)
Leading networking authority Douglas Comer presents a wide-ranging, self-contained tour of the concepts, principles, and technologies that enable today's Internet to support applications ranging from web browsing to telephony and multimedia.